Effect of Suspended Hydrated Lime Mineral Filler on the Physical Properties of Asphalt Binder - Mahdi, Lamya M. J.; Atif, Ruqaya M. (Engineering, Technology & Applied Science Research, 2025)
Although several studies have investigated the best additive to improve the properties of bitumen that contributes to asphalt pavement mixtures, selecting the best performing, cheapest, and most environmentally friendly material is not yet an easy task. Aging can be a chronic phenomenon that constantly threatens the durability and service life of asphalt pavement, and research efforts aim to mitigate its effects. Accordingly, this study selected a suspended and insoluble material as an additive to investigate its effect on the physical properties of asphalt binder before and after the aging process. Hydrated Lime Mineral Filler (HLMF) was added at different concentrations (2, 4, 6, 8, and 10 % by weight of asphalt) to investigate its ability to mitigate the effect of short-term aging. Penetration, softening point, and viscosity tests were performed on samples prepared under two conditions, short-term aging and non-aging. The results showed positive signs of improvement, with lower penetration values and higher softening point values achieved, as well as higher viscosity values measured at two standard elevated temperatures. The higher retained penetration values as well as the lower increment in Softening Point (SP), and Viscosity Aging Index (VAI) values showed that the suspended HLMF particles successfully enhanced the aging resistance of the asphalt binder. All AC-HLMF samples showed better performance than the unmodified AC asphalt sample. There were no significant performance variations for the selected HLMF concentrations, but AC-HLMF 6% was the best performer, recording a 9% RP and a 26% VAI improvement compared to base asphalt.